KORUPSI DAN KEGAGALAN ETIKA DALAM ADMINISTRASI PUBLIK: DAMPAK PADA PELAYANAN MASYARAKAT - Achmad Rifqi Azdi; Raul Hidayat Nurwahid; Hayat (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2024)
This study aims to analyse the impact of corruption on the effectiveness of public services in Indonesia from the perspective of public administration ethics. Corruption in the public sector not only harms state finances, but also reduces service quality and erodes public trust in government. The results show that corruption directly impacts the decline in efficiency, accessibility, and quality of public services. This causes dissatisfaction among the public who feel that services are not up to the expected standards. This research utilises the literature review method by examining previous studies on the impact of corruption on public services and how corruption reflects a failure to apply ethical values such as integrity, accountability and responsibility in public administration. Based on the findings, this study recommends strategic measures to combat corruption, including reform of the law enforcement system to reduce the level of corruption, increased transparency, and active involvement of the public in overseeing public services. These efforts are expected to realise better governance, improve the quality of public services, and restore public trust in government institutions.